New records of ectoparasites for Mexico and their prevalence in the montane shrew Sorex monticolus (Eulipotyphla: Soricidae) at Cerro del Mohinora, Sierra Madre Occidental of Chihuahua, Mexico - Acosta, Roxana; Guzmán-Cornejo, Carmen; Cisneros, Flor Angélica Quiñonez; Quiñonez, Angélica Annay Torres; Fernández, Jesús A. (Zootaxa, 2020)
The Flora and Fauna Protection Area (Área de Protección de Flora y Fauna—ÁPFF) Cerro del Mohinora, is the highest mountain in northern Mexico, reaching an elevation of 3,300 meters. It constitutes one of the last high-elevation islands of alpine and subalpine vegetation known in the Sierra Madre Occidental, in the extreme southwestern part of Chihuahua. The ÁPFF Cerro del Mohinora is located near the state border and limits with Durango and Sinaloa. This type of ecosystem located at high altitudes is in danger of disappearing since only 1% or less of its original extension remains; it is considered a refuge for species with boreal affinities (McDonald et al. 2011).